Environmental Politics Governmental Organization - Hanny Hafizah (International Journal on Social Science, Economics and Art, 2021)
In modern times the development of being one aspect keep moving and developing very quickly. Especially after the fall of the new order regime gave way to the days of reform. Both by the government and private, would promote development in Indonesia. Development is expected to be able to create for the public welfare, but there rarely development the desired instead not see norms and normal ethics which has. When a government may not take action and give apparent limits to limit development, then came institutions independent outside the government as WALHI which highlighted the cases. It this study tries to to decipher how the role of WALHI-SU Under Construction of a Watershed (DAS) Deli Medan City in North Sumatra. Methods used to research this is descriptive qualitative, this study attempts to see and solve problems with see the data and the facts of the phenomenon in which to day. Descriptive research is a process a problem solving investigated by describing or make clear had an object and the subject of study someone, and the community institutions. Research the role of WALHI-SU in development monitoring flow areas Watershed (DAS) Deli of the City of Medan this use some the skeleton theory in it as, the movement of social, suppressor and political group development expected to decipher the role of walhi easily and objective. In this research, writer view walhi in supervising local government is rally synergy power between a non-governmental organisation and organization the people oriented to values, encourage transforming social, facilitate communication and information between a non-governmental organisation.